Early Sport Specialization. (20th October 2021) - Agel, Julie; Post, Eric
Abstract : Early sport specialization has been recognized as a potential factor in the relationship between physical activity and health since the early 1970s. There is no universally agreed-upon terminology or definition for early sport specialization, but early sport specialization typically encompasses preteen athletes who play 1 sport competitively throughout the year or play on several teams within 1 season, leading to intensive participation without variation in physical activity. There is a limited number of comprehensive long-term outcome studies that have identified a potential link between early sport specialization and musculoskeletal injury or burnout. Methodologically sound prospective research looking at chronologic age and years of participation by sports played will help to answer whether there is an impact from early sport specialization on the relationship with successful participation and injury occurrence.